Tindakan Penyitaan Barang Bukti Dalam Penyidikan Tindak Pidana Penyalahgunaan Narkotika - Nella Maria Ulfa; Binov Handitya (Rampai Jurnal Hukum (RJH), 2024)
In the process of investigating narcotics crimes, confiscation has a very important role because the purpose of confiscation is to take over and/or keep under its control narcotics evidence for evidentiary purposes in investigations, prosecutions and trials. Therefore, the author is interested in discussing the implementation of the confiscation of narcotics evidence by Semarang Police investigators. The problems in this research are: 1) How is the confiscation of narcotics evidence carried out by Indonesian National Police investigators in the jurisdiction of the Semarang Police; 2) What are the consequences if drug evidence is damaged or lost. This research includes descriptive research to provide an overview of the normative provisions for narcotics crimes and the implementation of confiscation of evidence in narcotics cases at the investigation level at the Semarang Police. Based on the research results, it can be concluded that (1) The confiscation of evidence in drug cases during the investigation process at the Semarang Police is carried out according to procedures by showing a confiscation permit from the Head of the District Court, showing or displaying identification, showing the objects to be confiscated, making an official report. confiscation, conveying confiscation minutes and wrapping confiscated objects. (2) The risks and responsibilities for confiscation of damaged or lost evidence confiscated by Semarang Police investigators are: (a) Repairing it so that the evidence returns to its original condition at personal expense. (b) Replace lost evidence with the same or similar items. (c) In addition to compensation, administrative action and physical action are given, such as detention in a detention cell because he was negligent in lending evidence based on the results of the examination and trial for legal reasons. Abstrak Dalam proses penyidikan tindak pidana narkotika penyitaan memiliki peranan yang sangat penting karena tujuan dilakukannya penyitaan adalah untuk mengambil alih dan atau menyimpan dibawah penguasaannya barang bukti narkotika untuk kepentingan pembuktian dalam penyidikan, penuntutan dan peradilan. Oleh karena itu, penulis tertarik untuk membahas pelaksanaan penyitaan barang bukti narkotika oleh penyidik Polresta Semarang. Permasalahan dalam penelitian ini adalah: 1) Bagaimanakah pelaksanaan penyitaan barang bukti narkotika oleh Penyidik Kepolisian Negara Republik Indonesia di wilayah hukum Polresta Semarang; 2) Bagaimana akibat apabila barang bukti narkoba terjadi kerusakan ataupun hilang.Penelitian ini termasuk penelitian deskriptif untuk memberikan gambaran tentang ketentuan normatif tindak pidana Narkotika dan pelaksanaan penyitaan barang bukti kasus narkotika pada tingkat penyidikan di Polres Semarang. Berdasarkan hasil penelitian dapat disimpulkan bahwa (1) Pelaksanaan penyitaan barang bukti kasus narkoba dalam proses penyidikan di Polres Semarang, dilakukan sesuai prosedur dengan menunjukkan surat izin penyitaan dari Ketua Pengadilan Negeri, memperlihatkan atau menunjukkan tanda pengenal, memperlihatkan benda yang akan disita, membuat berita acara penyitaan, menyampaikan turunan berita acara penyitaan dan membungkus benda sitaan. (2) Resiko dan tanggung jawab penyitaan terhadap rusak atau hilangnya barang bukti yang disita oleh penyidik Polres Semarang, adalah : (a) Memperbaiki sehingga barang bukti tersebut kembali sesuai semula dengan biaya pribadi. (b) Mengganti barang bukti yang hilang dengan barang yang sama atau mirip. (c) Selain mengganti diberi tindakan administratif dan tindakan fisik seperti penahanan dalam sel tahanan karena telah lalai dalam meminjamkan barang bukti dengan berdasarkan hasil pemeriksaan dan sidang oleh alasan hukum.